Fig. 1 in Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland ... - Skovsted, Christian B.; Peel, John S. (Zenodo, 2007)
Fig. 1. Lower Cambrian localities in eastern Laurentia (A), map of Newfoundland indicating the Bonne Bay region (B) and simplified Lower Cambrian stratigraphy in western Newfoundland (C). ... : Published as part of Skovsted, Christian B. & Peel, John S., 2007, Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland, pp. 729-748 in Acta Palaeontologica Polonica 52 (4) on page 730, DOI: 10.5281/zenodo.13741171 ...